Pengaruh Tepung Ampas Bawang Putih terhadap Pertumbuhan Ayam Kampung Super Umur 3–10 Minggu - Putu Chandra Ayu Parwati; I Gusti Agus Maha Putra Sanjaya; Luh Suariani (Fakultas Pertanian, Universitas Warmadewa, 2026)
This study aimed to determine the effect of garlic waste flour supplementation in the ration on the growth performance of super native chickens aged 3–10 weeks. The experiment was conducted using a Completely Randomized Design (CRD) with five treatments and four replications. The treatments consisted of P0 (control, without garlic waste flour), P1 (2%), P2 (4%), P3 (6%), and P4 (8%) garlic waste flour inclusion levels. The observed variables were initial body weight, final body weight, body weight gain, feed consumption, and feed conversion ratio (FCR). Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test when significant differences were found. The results showed that garlic waste flour supplementation had no significant effect (P>0.05) on initial body weight, final body weight, and body weight gain. However, it significantly affected (P<0.05) feed consumption and FCR. The 8% inclusion level showed the best performance in improving feed efficiency. It can be concluded that garlic waste flour can be used up to 8% in super native chicken rations without negatively affecting growth performance.